2018
DOI: 10.1111/jfb.13589
|View full text |Cite
|
Sign up to set email alerts
|

Using passive acoustics to assess habitat selection by the brown meagre Sciaena umbra in a northern Adriatic Sea mussel farm

Abstract: Passive acoustic monitoring (PAM) of the brown meagre Sciaena umbra was conducted in a northern Adriatic Sea mussel farm. The level of acoustic activity was found to be constantly high from June to August before declining sharply in September and there was significantly higher acoustic activity in the structured habitats within the mussel farm than in the bare sandy bottom outside the farm. Results are discussed in the context of the use of this species as an indicator species of artificial rocky habitats alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The inlets now present artificial hard substrates in an otherwise soft and mobile sea floor, which increase habitat heterogeneity. It is known that these artificial structures can act as an attraction site for the brown meagre (Fabi, Panfili & Spagnolo, 1998;Bonacito et al, 2002;Colla et al, 2018). Along the Venice inlets, reproductive individuals have been previously acoustically identified (Picciulin et al, 2013), whereas the presence of the shi drum has been reported only anecdotally by local recreational fisherman.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The inlets now present artificial hard substrates in an otherwise soft and mobile sea floor, which increase habitat heterogeneity. It is known that these artificial structures can act as an attraction site for the brown meagre (Fabi, Panfili & Spagnolo, 1998;Bonacito et al, 2002;Colla et al, 2018). Along the Venice inlets, reproductive individuals have been previously acoustically identified (Picciulin et al, 2013), whereas the presence of the shi drum has been reported only anecdotally by local recreational fisherman.…”
Section: Study Areamentioning
confidence: 99%
“…Adult aggregations of shi drum generally occur along sandy beaches, mixed rock and sand surf-zones and subtidal reefs (Hutchings & Griffiths, 2005), features which characterize the study site. On the other hand, the local distribution of S. umbra is probably due to its preference for the artificial, hard structures that resemble its typical reproductive habitat, consisting of rocky reefs with holes and shelters close to soft substrates acting as feeding grounds (Fabi, Panfili & Spagnolo, 1998;Bonacito et al, 2002;Colla et al, 2018). To date, no research has focused on the species-specific abiotic habitat preferences (temperature, salinity, depth, water current) of the target species.…”
Section: The Ecological Requirements Of the Target Species And Their Relation To The Observed Fish Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial mapping of S. umbra based on their vocalisations has been proposed and successfully adopted in the Gulf of Venice (Italy) (Bonacito et al, 2002;Colla et al, 2018;Picciulin et al, 2013). In this study sound recordings were acquired using two or three simultaneously deployed drifting devices equipped with an EA-SDA14 compact autonomous recorder (RTSys®, France) and a HTI-92-WB (High Tech Inc.®) hydrophone with a flat sensitivity equal to −155 ± 3 dB re 1 V μPa−1 between 5 and 50 kHz.…”
Section: Acoustic Data Acquisition and Recording Protocolmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 4, 2020. ; https://doi.org/10.1101/2020.06.03.131326 doi: bioRxiv preprint the knowledge gaps about the brown meagre's ecology and reproductive behaviour and a few pioneering studies in the Gulf of Venice (Italy) using PAM for spatial monitoring (Bonacito et al, 2002;Colla et al, 2018;Picciulin et al, 2013b), there are no studies reporting the application and validation of this technique by environmental managers. The aims of this study were to underline the efficiency of PAM for the survey and management of S. umbra and its potential spawning grounds within and outside MPAs by mapping it's acoustic activity 1) along the coastline of three wide-ranging MPAs, 2) at large spatial scales (Northwestern Mediterranean), and 3) over two years in a no-take reserve.…”
Section: Introductionmentioning
confidence: 99%